STRATEGI PENGEMBANGAN KAMPUNG WISATA CODE JETISHARJO COKRODININGRATAN KOTA YOGYAKARTA - Pusparingga, Puspita; Yulianto, Daris (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
This research aims to describe and analyze the development strategy for Code Tourism Village in Jetisharjo Yogyakarta. This tourist destination is based on community empowerment that takes advantage of the beauty of the Code River. Even though it has great potential, the development of this tourist village is hampered by the lack of skilled human resources, inadequate facilities, and the impact of the Covid-19 pandemic which has significantly reduced the number of visitors. This research tries to formulate a development strategy using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), as well as looking at destination development using Cooper's theory including: (1) Attractions; (2) Accessibility; (3) Amenities; (4) Ancillary Service; and (5) Institutions. This research method is descriptive qualitative with data collection techniques in the form of in-depth interviews, field observations and documentation studies. The research results show that Code Tourism Village has a unique attraction in the form of a beautiful river ecosystem, culture-based attractions, and facilities such as homestays and weekly traditional markets. However, digital institutions and promotion still need to be improved. The recommended strategy is to strengthen government and community collaboration, provide human resource training, and utilize digital platforms for tourism promotion. By implementing this strategy, it is hoped that Code Tourism Village can develop into a leading destination in Yogyakarta and improve the welfare of the local community.Keyword: Strategy; Development; Tourism Village; Sustainable Tourism.